A Systematic Literature Review: Generalization in Solving Number Pattern Problems - Maula, Nyla Farhatul; Suryadi, Didi; Jupri, Al (FKIP Universitas Lampung, 2024)
Generalization is the process of identifying common characteristics in mental objects to find patterns, allowing for the application of general rules. It plays a crucial role in mathematics, being a fundamental aspect of mathematical thinking. Generalization is closely related to number patterns because number patterns can naturally lead to general expressions in generalizations. This study aims to review research on generalizations in number pattern material from 2004 to 2024. The research method uses a Systematic Literature Review which collects primary data that has been published in Sinta and Scopus-indexed journals. Data extraction is adjusted to the selection criteria so that 18 articles are collected. Data analysis follows a qualitative approach. Data grouping was carried out based on year of publication, level of education, research subject, journal index, demographics, methods, and generalization topics analyzed. Results show that 2015 and 2023 were key years for publications on this topic in reputable national and international journals. Researchers tend to focus on generalizations in number pattern problems at the junior high school level. Most studies use qualitative methods, exploring generalization strategies, representations, and processes. Keywords: generalization, number pattern, systematic literature review, mathematics, education.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp701-711